One‐year clinical evaluation of two high‐viscosity glass‐ionomer cements in class II restorations of primary molars. (7th November 2020) - Gok Baba, Merve; Kirzioglu, Zuhal; Ceyhan, Derya
Abstract: Background: Little information exists on the clinical performance of restorative materials on primary teeth of preschool children. This study aimed to evaluate clinical performance of compomer, glass‐hybrid‐added high‐viscosity glass‐ionomer cement and zinc‐added high‐viscosity glass‐ionomer cement materials in class ΙΙ restorations of primary molars. Methods: The study included 251 teeth of 57 patients aged 4–7 years with proximal caries in primary molars. The teeth were divided into three groups, and each restorative material was randomly distributed. Dyract XP, Equia Forte and ChemFil Rock materials were placed after cavity preparation and clinically evaluated at 3, 6, 9 and 12 months using modified United States Public Health Service criteria. Statistical analyses were performed using chi‐square and z tests. Results: At the end of 12 months, a total of three restorations in Dyract XP group, 22 in Equia Forte group and 11 in ChemFil Rock group failed in retention criteria. No statistically significant difference existed between retention, colour match and surface texture criteria of all groups at 3 and 6 months, but a statistically significant difference was found at 12 months ( P < 0.05). Conclusion: For class ΙΙ restorations of primary molars, the success of compomer material was superior to high‐viscosity glass‐ionomer materials.